Стримуючі чинники розвитку сільськогосподарських кооперативів у Грузії - Sanikidze, Hamlet (Dr. Viktor Koval, 2021)
Introduction. The lack of an appropriate methodological basis for creating agricultural cooperative system prevents the process of organizing formation of new agricultural cooperatives, which leads to an objective need to develop the organizational and economic basis for the formation and operation of agricultural cooperatives. In this regard, the research and study of theoretical aspects, analysis of objective conditions for the formation and operation of agricultural cooperatives, development of methodological provisions and practical recommendations to substantiate their organizational and economic mechanism, including matters of management, profit, price, credit, formation and distribution are topical to the issue and most of the components listed above are of great practical importance. Aim and tasks. The aim of the research is to develop scientific, organizational and economic basis for the establishment and operation of agricultural cooperatives in a multistructural economy. The objectives of the research are: identifying the essence of the cooperative, adding several principles to the formation and classification of agricultural cooperatives, determining the conditions and factors necessary for their creation. Results. Theoretical and regulatory aspects of formation and development of agricultural cooperatives were specified taking into account the introduction of new principles for their operation: mandatory creation of indivisible funds for innovative activities, agricultural producers’ interest and expediency for their participation in the associations; and classification of cooperatives in the production and service industries. Conclusions. Based on consideration of the integrated approach to the formation of cooperatives and farmers’ organizations, necessary documentation and calculation of economic efficiency, the methodological provisions developed in the process of the research on the establishment and operation of agricultural cooperatives will allow agricultural producers to approach the formation of necessary cooperatives skillfully, easily determine the absolute and specific tax burden of agricultural cooperatives.